STUDENTS’ PROBLEM IN NARRATIVE TEXT: WHAT DEALS AND WHAT TO DO? - Delsi Mitra (Humanitatis : Journal of Language and Literature, 2017)
One of the popular genres that taught at school is narrative text. Mostly, narrative text is delivering in three main aspects as already set in the 2013 curriculum; language feature, generic structure and social function. However, this paper will add a set of SFL (Systemic Functional Linguistics) that also become a measurement of students’ tasks. This paper is to employ descriptive qualitative. From the data, it found that the mostly mistake is the infinite term. Meanwhile, the three aspects (orientation, complication, and resolution) of the generic structure of a narrative story is completely stated in this narrative story. Furthermore, this paper will elaborate a new set for teaching narrative text that is called a problem-based approach (PSA) as the combination of task-based learning and problem-based learning.